Vertical transmission and humoral immune response following maternal infection with SARS-CoV-2: a prospective multicenter cohort study. (September 2022) - Massalha, Manal; Yefet, Enav; Rozenberg, Orit; Soltsman, Sofia; Hasanein, Jamal; Smolkin, Tatiana; Alter, Adi; Perlitz, Yuri; Nachum, Zohar
Abstract: Objective: To explore maternal humoral immune responses to SARS-CoV-2 infection and the rate of vertical transmission. Methods: A prospective cohort study was conducted at two university-affiliated medical centers in Israel. Women positive for SARS-CoV-2 reverse-transcription-polymerase-chain-reaction (RT-PCR) test during pregnancy were enrolled just prior to delivery. Levels of anti-SARS-CoV-2 spike-IgM, spike IgG, and nucleocapsid IgG were tested in maternal and cord blood at delivery, and neonatal nasopharyngeal swabs were subjected to PCR testing. The primary endpoint was the rate of vertical transmission, defined as either positive neonatal IgM or positive neonatal PCR. Results: Among 72 women, 36 (50%), 39 (54%) and 30 (42%) were positive for anti-spike-IgM, anti-spike-IgG, and anti-nucleocapsid-IgG, respectively. Among 36 neonates in which nasopharyngeal swabs were taken, one neonate (3%, 95% confidence interval 0.1–15%) had a positive PCR result. IgM was not detected in cord blood. Seven neonates had positive IgG antibodies while their mothers were seronegative for the same IgG. Anti-nucleocapsid-IgG and anti-spike-IgG were detected in 25/30 (83%) and in 33/39 (85%) of neonates of seropositive mothers, respectively. According to the serology test results during delivery with respect to the time of SARS-CoV-2 infection, the highest rate of positive maternal serology tests was 8 to 12 weeks post-infection (89% anti-spike IgG, 78% anti-spike IgM, and 67% anti-nucleocapsid IgG). Thereafter, the rate of positive serology tests declined gradually; at 20 weeks post-infection, only anti-spike IgG was detected in 33 to 50%. Discussion: The rate of vertical transmission of SARS-CoV-2 was at least 3% (95% confidence interval 0.1–15%). Vaccination should be considered no later than 3 months post-infection in pregnant women due to a decline in antibody levels.